The “Beautiful” in monuments: reflections on the aesthetics of the monument to Dona Domingas - Nunes, Fabíola Fraga; Miranda, Giuliano de; Cirillo, Aparecido José (Revista do Colóquio, 2025)
This article investigates one aspect of the research on the monument to Dona Domingas, specifically proposing an analysis of its sculptural representation. Despite its imagery portraying a large part of the population living on the outskirts of Vitória, the sculpture has little social acceptance due to the common perception of “beauty” by a large part of the population, and does not engage with the prevailing imagery of beauty, which largely considers the figure of the young man represented in the monuments as synonymous with beauty. We will shed light on the definitions of “beauty,” especially in the arts and philosophy, in order to understand the reasons why this monument faces this disconnection with those who should be indelibly linked to it.